EGALITARIANISM AS A PROBLEM OF SOCIAL JUSTICE IN CONDITIONS OF WAR - Abуsova, Mariya (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. The problem of social justice acquires particular significance under conditions of war, which transform not only political institutions and mechanisms of resource distribution, but also the normative conditions of justice itself. Contemporary egalitarian theories increasingly take into account vulnerability, dependency, contextual asymmetry, and unequal conditions of social existence. However, war radicalizes these asymmetries and raises the question of the limits of moral equality under conditions of collective survival. The aim and tasks of the study are to provide a philosophical analysis of the transformation of egalitarian justice in wartime society and to examine the tension between the principle of universal moral equality and structurally asymmetrical conditions of war. Research methods. The study combines historical-philosophical, comparative, hermeneutic, and normative-analytical approaches. Research results. It is demonstrated that classical egalitarian theories were predominantly formed within a symmetrical model of society based on institutional stability and universal social cooperation between formally equal subjects. Contemporary egalitarianism substantially revises these assumptions by focusing on vulnerability, relational dependency, and contextual asymmetry. At the same time, war transforms asymmetry into a structural principle of social organization. Particular attention is devoted to the concept of functional inequality, understood as an asymmetrical distribution of risks, obligations, access to protection, and social vulnerability arising from the necessity of maintaining collective survival in wartime society. The study also shows that war produces not only distributive inequality, but also asymmetry of political visibility, recognizability, and grievability of human life. Discussion. The proposed interpretation develops contemporary discussions on vulnerability, relational egalitarianism, just war theory, and the state of exception, while shifting attention toward the mechanisms through which wartime society distributes risks and moral recognition between different social groups. Conclusions. The study concludes that justice under wartime conditions cannot be reduced to the elimination of all asymmetry. The principle of moral equality does not disappear; however, it increasingly functions as a critical normative principle limiting permissible forms of wartime differentiation, domination, and dehumanization.